Genotypic variation of wheat (Triticum aestivum L.) in grain filling and contribution of culm reserves to yield - Islam, Md Amirul; Fakir, Md Soaliman Ali; Hossain, Md Alamgir; Sathi, Maria Akter (Bangladesh Journal of Botany, 2021)
To study the genotypic variation in the rate of grain filling and contribution of culm reserves to yield in wheat, an experiment was conducted consisting 12 popular cultivars of Bangladesh, viz., BARI Gom21 (Shatabdi), BARI Gom22 (Shufi), BARI Gom23 (Bijoy), BARI Gom24 (Prodip), BARI Gom25, BARI Gom26, Akbar (BAW 43), BARI Gom18 (Protiva), BARI Gom19 (Sourav), BARI Gom20 (Gourab), Agrani (BAW38), and Kanchan (BAW28). Tillers were sampled from anthesis to maturity to determine the changes in dry weights of different parts to examine the contribution of culm reserves to grain yield. The results in the experiment revealed that the grain yield varied from 2.61 to 5.35 ton/ha with the mean of 4.18 ton/ha. Among the cultivars BARI Gom24, BARI Gom26, BARI Gom19, and BARI Gom23 appeared as high yielders while Kanchan, Agrani, BARI Gom20, BARI Gom22 as the low yielders. Generally, high yielding cultivars showed higher total dry mass accumulation compared to low yielding ones. Moreover, high yielding cultivars also showed higher water soluble carbohydrates (WSCs) contents in culm at milk ripe stage than the low yielders. In general, contribution of culm WSCs to grain yield was more in high yielders than low yielders and it ranged from 2 to 29% of total grain weight. So, higher contribution of culm reserves resulted in higher grain yield of wheat.